The foraging behaviour of stingless bee Geniotrigona thoracica on star fruit - Mohmed Zaini, Nur Asilah (2017)
Department of Agriculture Malaysia has recorded the export of star fruit had dropped 73 % from 10395.1 metric tons in 2010, to only 2776.5 metric tons in 2012. An inadequate pollination rate is one of the factors that contribute to low yield. One of the effective ways of increasing the pollination rate is by having insect pollinators such as stingless bees in the star fruit farm. The study on the efficiency of stingless bee as star fruit pollinator is still lacking in Malaysia. Therefore the objectives of this study were: 1) to determine the frequency of forgers going out and coming back to the hive; 2) to investigate the average number flower visited and time taken per flower visit. The colonies of G. thoraccica stingless bee were obtained from Integrated Farm, Faculty of Agriculture UPM. The study consisted of two experiments: 1) observation of foraging time and 2) observation on pollination service. Three colonies of G. thoracica were selected for observation of foraging activity of stingless bee. Foraging bees were enumerated by using a manual tally counter to determine the number of individuals the flew in and out of their hive within a ten minute period each hour for each colonies from 0800 hours to1300 hours . Then ten G. thoracica foragers were selected randomly and marked using insect colouring on their thorax. The period of each flower visited by each marked forager was individually recorded by using stopwatch. The number of flowers visited by G. thoracica was also recorded in three minutes. Data for number of G. thoracica stingless bee flew out and into hive were analyzed using One-Way ANOVA at P=0.05. The foraging activity for each hours showed no significant difference (P > 0.05). However, the peak time foraging activity of G. thoracica was in between 0900 hrs until 1000 hrs. The highest number of flowers visited in three minute was 31 flowers while the lowest number flowers visited in was seven flowers. Meanwhile the longest average visited period for each flower is 12.88 seconds and the shortest average visited period for each flower is 2.72 seconds.